Spatial Variability of Soil Temperature in an Urban Area: a Case Study for a Medium-sized European City - Lehnert, Michal; Šimáček, Petr; Fiedor, David; Jurek, Martin (Geographica Pannonica, 2020)
Even though soil temperature in urban environment influences a range of processes, it has been studied rather sparsely in comparison with surface temperature or air temperature. Our research extends the soil temperature observation in Olomouc (Czechia) and uses semi-stationary measurement to describe detailed spatial variability of soil temperature in the area of a medium-sized Central European city. Differences in soil temperature 20 cm below grass-covered surface may exceed 3°C due to soil type, shadow cast by buildings and grass characteristics, which means that the representativeness of the data on soil temperature from a meteorological station within a city may be limited. Further research and a conceptual approach towards the study of soil temperature in urban landscape is needed.